Shareholder’s role in insolvency procedure - Vujic, Sanja (Riga Graduate School of Law, 2017)
The aim of this thesis is to analyze the position of the shareholder in a company when it is experiencing financial difficulties. The analysis will cover insolvency procedures in the U.S. and Bosnia and Herzegovina. The thesis will observe the shareholder’s role in the insolvency procedure, how many shareholders can influence the reorganization process and the possibility of the shareholder to retain participation in the reorganized company.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law; Shareholders rights